2013
DOI: 10.1155/2013/538376
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Parameters in Predicting Outcome of Patients with Hepatocellular Carcinoma Treated with Yttrium-90 Microsphere Radioembolization

Abstract: Background. In patients with hepatocellular carcinoma, selection criteria for transarterial hepatic selective internal radiotherapy are imprecise. Additionally, radiographic parameters to predict outcome of transarterial hepatic selective internal radiotherapy have not been fully characterized. Patients and methods. Computed tomography (CT) scans of 23 patients with unresectable primary hepatocellular carcinoma before and after transarterial hepatic selective internal radiotherapy with yttrium-90 microspheres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…8,9 In a study of 23 HCC patients treated with 90 Y, multivariate analysis demonstrated an association between prolonged progression-free survival and low LSF. 10 Considering the functional role of angiogenesis in metastasis, it is possible that LSF may be associated with the risk of metastatic spread of cancer cells from established primary and secondary liver tumors. Although previous studies have described the correlation between high LSF and more aggressive tumor characteristics, evaluation of LSF and its correlation with overall survival (OS) from 90 Y radioembolization have not been examined in detail.…”
mentioning
confidence: 99%
“…8,9 In a study of 23 HCC patients treated with 90 Y, multivariate analysis demonstrated an association between prolonged progression-free survival and low LSF. 10 Considering the functional role of angiogenesis in metastasis, it is possible that LSF may be associated with the risk of metastatic spread of cancer cells from established primary and secondary liver tumors. Although previous studies have described the correlation between high LSF and more aggressive tumor characteristics, evaluation of LSF and its correlation with overall survival (OS) from 90 Y radioembolization have not been examined in detail.…”
mentioning
confidence: 99%
“…This is particularly difficult in patients treated with SIRT since the radiation-induced changes in liver parenchyma impede objective response evaluation according to tumor size or contrast-enhancement. Furthermore, the radiological tumor response after SIRT can be delayed, or due to tumor necrosis and edema, show initial pseudo progression followed by stable or responsive disease afterwards [25].…”
Section: Discussionmentioning
confidence: 99%
“…The imaging evaluation consists of triphasic liver CT or MRI to evaluate variant vascular anatomy and to assess the extent and location of the hepatic tumor and its hypervascularity ( 7 14 ). CT scans may identify several characteristics of primary HCC that are associated with a favorable response to Y90-SIRT such as well-defined tumor margins, central hypervascularity pattern, and hepatopulmonary fraction ( 17 ).…”
Section: Pre-treatment Evaluationmentioning
confidence: 99%
“…Tumor response assessment following Y90-SIRT can be performed with conventional cross-sectional imaging such as CT and MRI ( 9 17 ). There is a lack of standardization of functional imaging in HCC and response assessment based on anatomical methods is considered as the standard ( 26 27 ).…”
Section: Tumor Response Assessment Following Y90-sirtmentioning
confidence: 99%